Farmers’ willingness to pay for alternative resource management practices in the Bale Eco-Region, Ethiopia: an application of choice experiment - Kefale, T.; Hagos, Fitsum; Rooijen, Daniel van; Haileslassie, Amare (Elsevier, 2021)
The purpose of this study is to investigate the preferences of people in the Bale Eco-Region (BER) for better ecosystem services and to calculate their mean Willingness to Pay (WTP) for selected attributes of conservation practices to maintain watershed's ecosystem functions, using a choice modeling approach. Results from reforestation attributes revealed that the average WTP for reforestation characteristics were 3,053 ($145.38), 2,516 ($119.83), and 1,827 ($87) Ethiopian Birr (ETB)/year for higher, medium, and low impact improvement scenarios respectively, to midland communities. Lowland respondents' mean WTP for exclosure attributes were estimated at 882 ($42), 1,558 ($74.19), and 2,383 ($113) ETB yearly for low, medium, and high impact improvement scenarios respectively. This indicates that respondents from both lowland and midland communities are willing to spend a substantial amount of resource and time (measured in terms of money) on to improve ES in the BER. The study provides valuable input to carry out a cost-benefit analysis of possible interventions conserving natural resources in the BER. Moreover, using this study was an important step for initiating the process of Payment for Ecosystem Services in the BER where local communities, in Ethiopia and beyond could contribute to rehabilitating Ecosystem Services.